2019
DOI: 10.1021/acs.organomet.9b00266
|View full text |Cite
|
Sign up to set email alerts
|

Terminal Phosphido Complexes of the Ru(η5-Cp*) Fragment

Abstract: In situ generation of the five-coordinate complex Ru(η 5 -Cp*)(PR 2 )(PPh 3 ) (2), via dehydrohalogenation of Ru(η 5 -Cp*)Cl(PR 2 H)-(PPh 3 ), has allowed its reactivity toward a range of small molecules to be compared with that of its well-studied analogue Ru(η 5 -indenyl)(PR 2 )(PPh 3 ) (1), in a study designed to assess the likelihood of variable hapticity in the chemistry of complex 1. Reactions of 2 with hydrogen, carbon monoxide, phenylacetylene, ethylene, acrylonitrile, and 1-hexene demonstrate enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…CDCl 3 (99.8 %), DCM-d 2 , and acetone-d 6 , were obtained from Cambridge Isotope Laboratories. P Cy 2 N Ph 2 , [25] [RuCl(Cp*)(PPh 3 ) 2 ], [26] [Ru(Cp)(P tÀ Bu 2 N Ph 2 )(MeCN)]PF 6 (1 a), [8c] [Ru(Cp)(P tÀ Bu 2 N Ph 2 )(MeCN)]PF 6 (1 c), [8c] and [Ru(Cp*)(P tÀ Bu 2 N Ph 2 )(MeCN)]PF 6 (2 a) [8c] were synthesized following literature procedures and the 1 H and 31 P{ 1 H} spectroscopic data matched literature values. Dry and degassed tetrahydrofuran (THF), diethyl ether (Et 2 O), and acetonitrile (MeCN) were obtained from an Innovative Technology 400-5 Solvent purification system and stored under N 2 .…”
Section: Methodsmentioning
confidence: 99%
“…CDCl 3 (99.8 %), DCM-d 2 , and acetone-d 6 , were obtained from Cambridge Isotope Laboratories. P Cy 2 N Ph 2 , [25] [RuCl(Cp*)(PPh 3 ) 2 ], [26] [Ru(Cp)(P tÀ Bu 2 N Ph 2 )(MeCN)]PF 6 (1 a), [8c] [Ru(Cp)(P tÀ Bu 2 N Ph 2 )(MeCN)]PF 6 (1 c), [8c] and [Ru(Cp*)(P tÀ Bu 2 N Ph 2 )(MeCN)]PF 6 (2 a) [8c] were synthesized following literature procedures and the 1 H and 31 P{ 1 H} spectroscopic data matched literature values. Dry and degassed tetrahydrofuran (THF), diethyl ether (Et 2 O), and acetonitrile (MeCN) were obtained from an Innovative Technology 400-5 Solvent purification system and stored under N 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies of the generation and reactivity of Ru­(η 5 -Cp*) phosphido complexes demonstrated increased substitutional lability relative to the analogous indenyl complexes due to the greater electron density at Ru and increased steric crowding from the Cp* ligand . This lability presents an opportunity for increasing the rate of turnover-limiting product substitution in catalysis, relative to the indenyl system, although it can make it challenging to isolate discrete mixed ligand complexes, since “simple” ligand-exchange reactions often lead to inseparable equilibrium mixtures of complexes resulting from variable degrees of substitution.…”
Section: Resultsmentioning
confidence: 99%
“…This lability presents an opportunity for increasing the rate of turnover-limiting product substitution in catalysis, relative to the indenyl system, although it can make it challenging to isolate discrete mixed ligand complexes, since “simple” ligand-exchange reactions often lead to inseparable equilibrium mixtures of complexes resulting from variable degrees of substitution. Phosphido ligands at the Ru­(η 5 -Cp*) core are also more basic, or nucleophilic, than those at Ru­(η 5 -indenyl), which is likely to enhance the rate of the (already fast) conjugate addition step in catalysis relative to the indenyl system. However, collectively, these features (increased substitutional lability and P-basicity) precluded isolation of the direct Cp* analogue of 1 , even with the mixed phosphine precursor Ru­(η 5 -Cp*)­Cl­(PPh 2 H)­(PPh 3 ) in hand (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Ruthenium phosphido complexes gave similar products on reaction with various small molecules (Lewis bases, Bronsted acids, H 2 , alkenes, and alkynes), regardless of the nature of the supporting ligand (i.e., indenyl vs Cp*; Scheme ). , For example, reaction of either 20 or 22 with ethylene gives the cycloaddition products 21 and 23 , respectively. A lower kinetic barrier with the Ind complex 20 was not apparent since both products 21 and 23 were formed within seconds.…”
Section: Influence Of Srls On Fundamental Organometallic Reactionsmentioning
confidence: 99%